2014
DOI: 10.2136/sssaj2014.05.0200
|View full text |Cite
|
Sign up to set email alerts
|

Hydropedological Assessments of Parcel-Level Infiltration in an Arid Urban Ecosystem

Abstract: soil morphology and correspondent hydrologic data can contribute to qualifying and quantifying urban soil suitability and capacity to cycle stormwater runoff. We put particular emphasis on the possibility that residential parcels may manage their own stormwater on pervious yard areas. We assessed the morphology of Aridisol pedons (as deep cores to approximately the 3.6-m depth) via soil taxonomy, performed in situ measurements of infiltration, and measured subsoil hydraulic conductivity in two desert parks, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Urban soils undergo processes that vastly alter hydrology at the anthropogenic time scale, e.g., a demolition that alters soil conditions in under 1 week. Similarly, the variation in urban soil hydrology at the spatial scale can vary at the submeter scale (Shuster et al 2014(Shuster et al , 2015, making even the highly interpolated mapping efforts of SSURGO inadequate. This begs the question: are tools like USDA Rosetta or soil hydrologic data obtained from either the NSWC or SSURGO adequate for modeling hydrologic responses of urban systems?…”
Section: Introductionmentioning
confidence: 99%
“…Urban soils undergo processes that vastly alter hydrology at the anthropogenic time scale, e.g., a demolition that alters soil conditions in under 1 week. Similarly, the variation in urban soil hydrology at the spatial scale can vary at the submeter scale (Shuster et al 2014(Shuster et al , 2015, making even the highly interpolated mapping efforts of SSURGO inadequate. This begs the question: are tools like USDA Rosetta or soil hydrologic data obtained from either the NSWC or SSURGO adequate for modeling hydrologic responses of urban systems?…”
Section: Introductionmentioning
confidence: 99%
“…Though we focus on the partitioning of rainfall between infiltration and surface runoff, detention capacity may be indirectly altered through deep drainage and evapotranspiration 25,51 . As vegetation intercepts rainfall that would otherwise reach impervious areas 21 , the presence of vegetation on vacant parcels may amplify the RDT of these areas.…”
Section: Discussionmentioning
confidence: 99%
“…The urban subsurface will also shape the efficacy of vacant parcels to serve as stormwater resources 17,40,51 . However, the impact of subsurface characteristics and below-ground hydrologic processes (e.g., deep drainage) on detention capacity represents a major source of uncertainty because subsurface hydrologic data are limited in most urban areas ( Supplementary Note 2).…”
Section: Discussionmentioning
confidence: 99%
“…We measured both infiltration and drainage rate of soils in permeable areas of the study area as described in Shuster et al () and reported in Hoard et al (). Infiltration rate was measured at 6‐m intervals along two parallel 55‐m transects of permeable, fallowed areas with tension infiltrometers set to approximately 2 cm of suction head.…”
Section: Settingmentioning
confidence: 99%